Envelope glycoproteins from biologically diverse isolates of immunodeficiency viruses have widely different affinities for CD4. - Ivey-Hoyle, M (1991)
The envelope glycoprotein gp120 of primate immunodeficiency viruses initiates viral attachment to CD4+ cells by binding to the CD4 antigen on host cell surfaces. However, among different CD4+ cell types, different viruses display distinct host cell ranges and cytopathicities. Determinants for both of these biological properties have been mapped to the env gene. We have quantitatively compared the CD4 binding affinities of gp120 proteins from viruses exhibiting different host cell tropisms and cytopathicities. The viral proteins were produced by using a Drosophila cell expression system and were purified to greater than 90% homogeneity. Drosophila-produced gp120 from T-cell tropic human immunodeficiency virus type 1 (HIV-1) BH10 exhibits binding to soluble recombinant CD4 (sCD4) and syncytia inhibition potency identical to that of pure authentic viral gp120. Relative to the affinity of HIV-1 BH10 gp120 for sCD4, that of dual tropic HIV-1 Ba-L is 6-fold lower, that of restricted T-cell tropic simian immunodeficiency virus mac is 70-fold lower, and that of noncytopathic HIV-2 ST is greater than 280-fold lower. Thus, viruses that utilize CD4 for infection do so by using a remarkably wide range of envelope affinities. These differences in affinity may play a role in determining cell tropism and cytopathicity.